2016
DOI: 10.18533/ijbsr.v6i6.947
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Aid and Economic Growth: A Panel Cointegration for Selected Turkic Republics

Abstract: <p>The paper highlights the many needs/goals of stake holders in the organisation and closely examines the well-worn believe that the main role of managers is to motivate their subordinates. Argument was proposed as to why this view is not appropriate in today’s organisations. The driving force for most employees, whose mobility and employability has been enhanced by ICT and globalization, is the extent to which the employing organisations is able to articulate their needs and meet them. To motivate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Despite the positive externality effect of foreign aid on economic growth, empirical evidence on this relationship remains inconclusive. Some studies have reported that foreign aid stimulates economic growth (Balcioglu, 2016;Bjørnskov, 2019;Rahnama et al, 2017;Magesan, 2016;Mohapatra et al, 2016;Moolio and Kong, 2016;Yiew and Lau, 2018). Others have reported either a negative or no significant relationship between foreign aid and economic growth (Adedokun, 2017;Mustafa et al, 2019;Hussain et al, 2018;Niyonkuru, 2016;Pohwani et al, 2019;Quy, 2016;Tang and Bundhoo, 2017;Weerasingha and Mustafa, 2019).…”
Section: Empirical Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Despite the positive externality effect of foreign aid on economic growth, empirical evidence on this relationship remains inconclusive. Some studies have reported that foreign aid stimulates economic growth (Balcioglu, 2016;Bjørnskov, 2019;Rahnama et al, 2017;Magesan, 2016;Mohapatra et al, 2016;Moolio and Kong, 2016;Yiew and Lau, 2018). Others have reported either a negative or no significant relationship between foreign aid and economic growth (Adedokun, 2017;Mustafa et al, 2019;Hussain et al, 2018;Niyonkuru, 2016;Pohwani et al, 2019;Quy, 2016;Tang and Bundhoo, 2017;Weerasingha and Mustafa, 2019).…”
Section: Empirical Literaturementioning
confidence: 99%
“…In an interesting empirical analysis by Mallik (2008) on why Africa has not broken the poverty chain in spite of the heavy inflow of foreign aid, the study investigated the six worst countries living in poverty in Africa that dependent hugely on foreign aid, and concluded that foreign aid had a negative effect on economic growth based on the cointegration analytical technique. Balcioglu (2016) used panel cointegration and unit root methods to examine the role of foreign aid on economic growth in Azerbaijan, GA, Kazakhstan, Kyrgyzstan, Turkmenistan and Uzbekistan for 1992-2014 and concluded that foreign aid drives economic growth. Moolio and Kong (2016) studied the relationship between foreign aid and economic growth in Cambodia, Lao, people's democratic republic (PDR), Myanmar and Vietnam between 1997 and 2014.…”
Section: Empirical Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…A long-run positive correlation showed between the aid-growth relationships [20]. Another study [21] exposed that external capital flows, such as aid, had a positive impact on economic growth. Foreign aid's influence on the economic growth evaluated and outcomes indicated a positive and significant role of aid in the progression of economic growth in Vietnam [22].…”
Section: Research Elaborationsmentioning
confidence: 99%
“…The coefficients of FDI and ODA per capita have a positive impact on GDP growth as expected. Balcioglu (2016) has conducted a research on the foreign aid and economic growth, a panel cointegrationfor selected Turkic Republics. The study indicates the long-run relationship between foreign aid and real economic growth for the period 1992-2014.…”
Section: Literature Reviewmentioning
confidence: 99%